EFEKTIVITAS NEURO LINGUISTIC PROGRAMMING DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK: SYSTEMATIC LETERATURE REVIEW - Hana Novyana; Busmayaril; Defriyanto (STAI Ma'had Aly Al-Hikam Malang, 2025)
This research aims to examine the effectiveness of Neuro Linguistic Programming (NLP) in increasing learning motivation through a Systematic Literature Review (SLR) approach. The research method was conducted by reviewing scientific literature that discusses the application and effectiveness of NLP in the context of increasing learning motivation. The articles analysed in this study were scientific publications published between 2020 and 2025. The article search process was conducted through electronic databases, resulting in a total of 994 articles. After removal of duplicates, 900 articles were further screened. At the initial screening stage, 508 articles were eliminated because they did not fulfil the inclusion criteria, such as not being systematic research articles, being book chapters, conference abstracts or short reviews. A total of 332 articles were then thoroughly evaluated, and 322 articles were excluded due to irrelevant topics or duplications that were not previously detected. Finally, 21 articles were selected for analysis in a qualitative synthesis. The findings of this study show that NLP has a wide range of applications in enhancing learning motivation, especially in the use of techniques such as anchoring, reframing, and swish patterns in modifying individuals' learning mindsets and behaviours. In addition, the results provide practical guidance for educational researchers and practitioners in selecting relevant NLP foci, such as the purple cluster which is directly related to learning motivation. The study also recommends further exploration of interactions between NLP clusters, such as the relationship between strengthening metacognition and increasing motivation, as well as the integration of NLP communication techniques in other psychological interventions. Thus, this research is expected to enrich the scientific literature related to NLP and become a reference in the development of NLP-based learning motivation enhancement strategies